PENGELOLAAN HUTAN KOTA: BERDASARKAN ASPEK EKOLOGI DAN ASPEK SOSIAL (Kasus di Hutan Kota-2 BSD City Kota Tangerang Selatan) - Iriani, Siti Pratiwi (Bumi Lestari, 2018)
This study was conducted at Urban Forest BSD-2 in South Tangerang City. This study aims to analyze: the distribution of vegetation types; microclimatic conditions as determinants comfort index; and relationship between environmental and awareness with behavior. Distribution of vegetation analysis found 30 species with number of the erect of trees 245 individuals. The result of the vegetation analysis shows that the erect of density the highest the growth rate of seedlings (3500 individual/ha). Diversity of vegetation types in Urban Forest-2 BSD City including fairly the diversity. The results of analysis carbon absorption that type of Albizia sp, type of Samanea saman, and type of Spatodea campanulata have the average value which high in CO  absorption high as 3,16 tons/ha, 2,31 tons/ha, and 2,28 ton/ ha. The microclimate analysis showed that the Urban Forest-2 BSD City have index environmental comfort with the category the half uncomfortable. The result of statictic test proved there was unidirectional relationship between knowledge and awareness with behavior of urban forest management. Suggestion research is urban forest management should be emphasized on the ecological aspects and social aspects.